1993
DOI: 10.1021/bi00065a007
|View full text |Cite
|
Sign up to set email alerts
|

Transcription termination factor rho: The site of bicyclomycin inhibition in Escherichia coli

Abstract: Bicyclomycin is a novel, commercially important antibiotic. Information concerning the site of bicyclomycin inhibition in Escherichia coli has been obtained by the production of bicyclomycin resistant mutants by UV irradiation. Selection by growth in the presence of bicyclomycin of a plasmid clone library generated from a highly resistant mutant in recipient antibiotic-sensitive host cells (E. coli strain W3350) has led to the characterization of three different plasmids that confer drug resistance, which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
133
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 25 publications
(39 reference statements)
6
133
0
Order By: Relevance
“…The drug bicyclomycin is a known inhibitor of Rho factor (37). Mutants resistant to the drug were isolated and characterized previously (35).…”
Section: Resultsmentioning
confidence: 99%
“…The drug bicyclomycin is a known inhibitor of Rho factor (37). Mutants resistant to the drug were isolated and characterized previously (35).…”
Section: Resultsmentioning
confidence: 99%
“…Zwiefka et al (24) found that the antibiotic bicyclomycin (bicozamycin), an inhibitor of the growth of several gramnegative bacterial species (24), interferes with the functions of Rho factor, a protein largely responsible for factor-dependent transcription termination (15,16). They performed in vitro analyses demonstrating that bicyclomycin inhibited the poly (C)-stimulated ATPase activity of Escherichia coli Rho factor (24).…”
mentioning
confidence: 99%
“…They performed in vitro analyses demonstrating that bicyclomycin inhibited the poly (C)-stimulated ATPase activity of Escherichia coli Rho factor (24). They also isolated bicyclomycin-resistant mutants and showed that these mutants had alterations of Rho factor that conferred resistance to the drug both in vivo and in vitro (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While Rho is essential for viability in many Gram-negative organisms, Gram-positive organisms appear to be less dependent on it, although it is important in preventing transcription of noncoding RNA in the latter and has activity against Micrococcus luteus (165,166). Bicyclomycin is the only known antibiotic to target Rho, and it does not affect RNA or ATP binding to Rho but does inhibit Rho-dependent transcription termination and ATP hydrolysis (167)(168)(169). Substitutions in E. coli Rho residues L208, M219, S266, and G337 conferred resistance to bicyclomycin, suggesting that Rho was the binding target of bicyclomycin (170,171).…”
Section: Termination Factor Rhomentioning
confidence: 99%